Digitalization of Economic Management Processes in the Context of the Land Policy of Northern Kazakhstan - M. А. Ualieva; A. B. Maydirova (Экономика: стратегия и практика)
In the context of the continuous economic development of the Republic of Kazakhstan within the framework of the country’s popularized integration into the EAEU, increasing the level of digitalization in the context of science, technologies of state, and business management is becoming increasingly important. The article aims to consider the transformation of land policy management on the example of the Northern region of the Republic of Kazakhstan based on digitalization by assessing the effectiveness and availability of the Qoldau.kz service. In the course of writing the work, an author’s study was carried out using the Varimax method, aimed at determining the key factors characterizing the effectiveness of the Qoldau.kz service. The study results confirm the interconnection of critical aspects of the digital transformation of public administration in the context of the implementation of land policy in Northern Kazakhstan through the optimization of the Qoldau.kz service. The study results also determine the relationship between the low number of active users of the site and the complexity of its device, the need to have special practical skills, and the high cost of maintenance. To optimize the operation of the service in the context of land policy management, the authors proposes recommendations to simplify the process of obtaining a benefit, reduce the cost of service, minimize the corruption component in the allocation of subsidies, and the need to increase the popularity of the service among key recipients of services.